Next-Generation Lipids in RNA Interference Therapeutics - Rietwyk, Stephanie; Peer, Dan (ACS nano, 2017)
RNA is emerging as a potential therapeutic modality for the treatment of incurable diseases. Despite intense research, the advent to clinical utility remains compromised by numerous biological barriers, hence, there is a need for sophisticated delivery vehicles. In this aspect, lipid nanoparticles (LNPs) are the most advanced platform among nonviral vectors for gene delivery. In this review, we critically review the literature and the reasons for ineffective delivery beyond the liver. We discuss the toxicity issues associated with permanently charged cationic lipids and then turn our attention to next-generation ionizable cationic lipids. These lipids exhibit reduced toxicity and immunogenicity and undergo ionization under the acidic environment of the endosome to release the encapsulated payload to their site of action in the cytosol. Finally, we summarize recent achievements in therapeutic nucleic acid delivery and report on the current status of clinical trials using LNP and the obstacles to clinical translation.